Visible-Light-Mediated Trifluoroethylation of N-Arylacrylamides with Trifluoroethyl Iodide: Synthesis of CF3-Containing Oxindoles - Fu, Weijun; Zhu, Mei; Zou, Guanglong; Xu, Chen; Wang, Zhiqiang (Synlett, 2014)
A practical and unified strategy has been described for the preparation of CF3-containing oxindole derivatives using a visible-light-promoted trifluoroethylation reaction of N-arylacrylamides with trifluoroethyl iodide. These reactions could be carried out at room temperature in good to excellent chemical yields with good functional-group tolerance.
Keywords: trifluoroethylation; alkenes; oxindole; photoredox; radical reactions